3D CBCT Evaluation of Condyle Position in Skeletal Class I & Class III Growing Subjects - Mishra, Rajiv Kumar; Kharbanda, Om Prakash; Balachandran, Rajiv (Orthodontic Journal of Nepal, 2017)
Introduction: Evaluation of temporo-mandibular joint (TMJ) anatomy and function is an essential part of orthodontic diagnosis and treatment planning. It has been hypothesized that dental and skeletal malocclusions alter the functional loading of TMJ which can affect joint morphology. Objective: Three dimensional (3D) evaluation of condylar position using CBCT in skeletal Class I and Class III growing subjects. Materials & Method: CBCT images of ten growing skeletal Class I & ten Class III patients in the age range of 7-14 years were analyzed. 3D condylar position were evaluated representing antero-posterior, vertical, laterolateral position of condyle, axial condylar angle and coronal condylar angles which were measured in axial, coronal and sagittal sections using Dolphin Imaging software. Antero-posterior and vertical difference of right and left condyle were measured in axial and coronal sections respectively. Result: Paired t-Test revealed no significant difference between right and left sides of condyle in skeletal Class I as well as Class III subjects. Independent t-test and Mann-Whitney U test showed no significant difference between position of condyle in Class I and Class III subjects. Conclusion: 3D CBCT analysis shows no significant difference in condylar position of skeletal Class I and Class III subjects.